A Review on Land Use in the Malaysian State of Sarawak, Borneo and Recommendations for Wildlife Conservation Inside Production Forest Environment - Hon, Jason; Shibata, Shozo (Borneo Journal of Resource Science and Technology, 2016)
The Malaysian state of Sarawak, which lies in the island of Borneo, is rich in plant and animal diversity, and forms one of the global biodiversity hotspots. The major land uses include logging, agriculture and forest plantations. Deforestation and degradation of forests are occurring at a rate of 0.64% annually, largely due to expansion of oil palm plantations which increases at an average rate of 10.2% annually. More areas are being converted into forest plantations, which accounts for 3.25% of the total forested area. On the other hand, protected areas remain small, representing only 6.64% of total forested area or 4.23% of the total land area, and are located far apart. The bulk of forests are subjected to logging and many areas may be converted in the future to other land use such as agriculture. Furthermore, logging has been a major economic activity, and will continue to be so in the future. Hence, the network of production forests become crucial for wildlife and working with logging companies in this aspect is a realistic approach towards wildlife conservation. Some measures proposed include encouraging collaborative research in production forests; making sustainable forest management practices mandatory; creating buffer zones in areas adjacent to protected areas; and maintaining maximum connectivity of habitat for wildlife.